Pengaruh Pemberitaan Isu Miras Lokal di Media Online Terhadap Opini Masyarakat di Bangil - Putri Roudhotul Jannah Firdausy; Moh. Edy Marzuky (Brand Communication, 2024)
Liquor (alcohol) contains ethanol and is dangerous to health. The alcohol case in May 2023 in Bangil District caused deaths and had serious impacts on society. In Indonesia, alcohol is also a big problem with many cases of death due to consuming alcoholic drinks (alcohol) and mixed drinks. This incident was published by online mass media by describing the related facts and their impact. This research aims to determine the influence of online mass media coverage of the alcohol case on public opinion. Where public opinion is the attitudes and tendencies of society to act which are influenced by mass media framing. This research is included in the type of quantitative research. The data collection technique used in this research used a survey method by distributing 100 questionnaires in Bangil sub-district. The analytical method in this research uses the SPSS 23.0 test. The results of data analysis and hypothesis testing that have been carried out show that online mass media reporting variables have a positive influence on public opinion. This is proven by the significance value (0.000 < 0.05) and obtained F count > F table (47.104 > 3.94). Partial reporting has a positive and significant influence on public opinion. This is proven by a significance value of 0.00 at a significance level of 5% and obtained t count > t table (6.863 > 1.66071).